The Effect of Edmodo Based E-learning and Learning Independence on Islamic Religious Learning Outcomes For Grade VIII in Junior High School 7 Medan Country - Mardianto Mardianto; Mahariah Mahariah; Sri Suharti (International Journal Of Education, Social Studies, And Management (IJESSM), 2022)
This study aims to (1) find out the results of students' Islamic religious learning between groups taught with Edmodo-based E-learning higher than the results of students' Islamic religious learning taught with WhatsApp. (2) knowing the learning outcomes of Islamic students among groups of students who have higher learning independence than Islamic religious learning outcomes of students who have low learning independence; (3) To find out the influence between Edmodo-based E-learning and learning independence on the learning outcomes of Islamic students. This type of research is a quantitative research using the quasi-design of experiments. The population of this study is a class VIII student of SMP Negeri 7 Medan with a sample of class VIII C with as many as 33 students as an experimental class and class VIII A with as many as 32 students as a control class. Data collection uses tests and questionnaires and data analysis using a two-track ANOVA. The results showed that the results of learning the Islamic religion of students taught with Edmodo were higher than the results of learning Islamic religion students who were taught with WhatsApp. Islamic religious learning outcomes of students who have high learning independence are higher than the results of Islamic religious learning students who have low learning independence. There is an interaction between Edmodo and learning independence towards the results of learning Islamic religion students in grade VIII of SMP Negeri 7 Medan.